2019
DOI: 10.11648/j.ijber.20190803.11
|View full text |Cite
|
Sign up to set email alerts
|

Share Centralization, Investor Sentiment and Firm Performance

Abstract: The purpose of this paper is to identify how internal corporate governance and external investor sentiment impacts the operating performance of the firm. The corporate governance mechanism affects the firm's operating activities, and transfers its results to outside investors by public financial reports. Since the universal uninformed investors could only identify the firm's net income instead of accrual earnings, this paper reflects the "visible" accounting number to represent investors' received information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…This is an indication that investors are not always rational in Nigeria, and their irrational investment decision significantly influences stock trading in the country. This result agrees with studies that found significant positive relationship between investors' sentiment and stock performance among emerging and developing countries (Dalika &Yudhvir, 2015;Asian Naik & Padhi, 2016;Alajekwu, Obialor, Okoro & Ibenta, 2017;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). On the other hand, the finding from this study disagrees with studies that found no significant relationship between investors' sentiment and stock trading (Zainudin, Zaki, Hadi, Hussain & Kantakji, 2019).…”
Section: Conclusion and Recommendationssupporting
confidence: 71%
See 2 more Smart Citations
“…This is an indication that investors are not always rational in Nigeria, and their irrational investment decision significantly influences stock trading in the country. This result agrees with studies that found significant positive relationship between investors' sentiment and stock performance among emerging and developing countries (Dalika &Yudhvir, 2015;Asian Naik & Padhi, 2016;Alajekwu, Obialor, Okoro & Ibenta, 2017;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). On the other hand, the finding from this study disagrees with studies that found no significant relationship between investors' sentiment and stock trading (Zainudin, Zaki, Hadi, Hussain & Kantakji, 2019).…”
Section: Conclusion and Recommendationssupporting
confidence: 71%
“…The birth of behavioural finance (otherwise behavioural economics) in the 1990s has been on the rise in empirical literature that has sought to determine whether stock trading is driven by investors' sentiments. There is a consensus in the literature that sentiment influences market performance among emerging markets (Dalika &Yudhvir, 2015;Naik &Padhi, 2016;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). These studies corroborate findings from Alajekwu, Obialor, Okoro and Ibenta (2017) which found that sentiment significantly influences market performance in Nigeria.…”
Section: 0supporting
confidence: 68%
See 1 more Smart Citation
“…For linear correlation theory, views differ. Some researchers, such as Heitor [7], and Cheng [8], hold the positive linear correlation theory view that centralized management can significantly drive firm performance. For views in favor of negative linear correlation, studies such as Mauricio J et al (2019), Madhavi et al (2016), and Madhavi et al (2016) argue that removal of corporate centralization can raise the efficiency of investments and improve firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Short-term interest rate changes occur in response to developments in the economy in terms of both domestically and internationally such as local or international economic and political crises, changes in central bank policy rate, inflation, and expectations for economic growth (Joslin & Konchitchki, 2018). On the other hand, it is widely accepted that changes in short-term interest rates also have an impact other macroeconomic variables such as economic growth, unemployment and balance of payments.…”
Section: Introductionmentioning
confidence: 99%